Simple method to the dynamic modeling of industrial robot subject to constraint - Liu, Jia; Liu, Rong (Advances in mechanical engineering, 2016)
It is a common movement type in industrial production for the end-effector of industrial robot executing tasks according to desired track. High nonlinearity and coupling are shown from the dynamic characteristic of industrial robot because of the constrained relationship brought by desired task. Therefore, it is difficult to establish dynamical equation with traditional Lagrange equation. Aiming at the dynamics modeling of industrial robot subject to constraint, the additional torque and dynamical equation of industrial robot subject to some desired trajectory is acquired based on the famous Udwadia–Kalaba equation in analytical mechanics field. The simple approach overcomes the disadvantage of obtaining dynamical equation from traditional Lagrange equation by Lagrange multiplier. But the numerical results obtained by integrating the constrained dynamic equation yield the errors. A numerical algorithm is proposed to reduce the errors by modifying the derived dynamic equation. The simulation results prove that the modified algorithm can be more precisely utilized in dynamics modeling of industrial robot subject to constraint.